If x= 9+4 (root 5) then find (root x) - 1/ (root x)PLeaseee answer fasst! needed at the moment! :)

x=9+4√5

√x - 1/√x = (x-1)/√x

=> ( 9+4√5 - 1) / √(9 + 4√5 )

=>(8 + 4√5) / (4 + 5 + 4*5)

=> 4( 2 + √5) / √(22 + √52 + 2*2*√5)

=>4 ( 2 + √5) / √ (2 + √5)2

=>4(2+√5) / (2+ √5)

=> 4 (Ans)

thumbs up plz

• 35

x=9+4√5

√x - 1/√x = (x-1)/√x

=> ( 9+4√5 - 1) / √(9 + 4√5 )

=>(8 + 4√5) / (4 + 5 + 4*5)

=> 4( 2 + √5) / √(22 + √52 + 2*2*√5)

=>4 ( 2 + √5) / √ (2 + √5)2

=>4(2+√5) / ±(2+ √5)

=> 4 or -4 (Ans)

thumbs up plz

• 7

x=9+4√5

√x - 1/√x = (x-1)/√x

=> ( 9+4√5 - 1) / √(9 + 4√5 )

=>(8 + 4√5) / (4 + 5 + 4*5)

=> 4( 2 + √5) / √(22 + √52 + 2*2*√5)

=>4 ( 2 + √5) / √ (2 + √5)2

=>4(2+√5) /+-(2+ √5)

=> 4 (Ans)

• 2

sorry, theres a correction,

x=9+4√5

√x - 1/√x = (x-1)/√x

=> ( 9+4√5 - 1) / √(9 + 4√5 )

=>(8 + 4√5) / (4 + 5 + 4*5)

=> 4( 2 + √5) / √(22 + √52 + 2*2*√5)

=>4 ( 2 + √5) / √ (2 + √5)2

=>4(2+√5) /+-(2+ √5)

=> 4 or -4 (Ans)

• 0

thank q debasmita

• -3

whole root of 9 - 4 (root 5)

• -1
How did u make (2 root5)2 to 2root5???? At last
• -2
x=9+4√5 √x - 1/√x = (x-1)/√x => ( 9+4√5 - 1) / √(9 + 4√5 ) =>(8 + 4√5) / (4 + 5 + 4*5) => 4( 2 + √5) / √(22 + √52 + 2*2*√5) =>4 ( 2 + √5) / √ (2 + √5)2 =>4(2+√5) / ±(2+ √5) => 4 or -4 (Ans)
• -2
here is the answer for the question .... it is easy but is a bit complicated one.. ■■ HOPE HELPS ■■

• 8
What are you looking for?